2012
DOI: 10.1126/scitranslmed.3004334
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Evaluation of Minnelide as a Therapeutic Agent Against Pancreatic Cancer

Abstract: Pancreatic cancer is one of the most lethal human malignancies with an all-stage 5-year survival frequency of <5%, which highlights the urgent need for more effective therapeutic strategies. We have previously shown that triptolide, a diterpenoid, is effective against pancreatic cancer cells in vitro as well as in vivo. However, triptolide is poorly soluble in water, limiting its clinical use. We therefore synthesized a water-soluble analog of triptolide, named Minnelide. The efficacy of Minnelide was tested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
247
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(251 citation statements)
references
References 34 publications
4
247
0
Order By: Relevance
“…However, for most cancer cells, the LD 50 for triptolide has been found to be 100 nmol/liter (37), at which XPB remains unaffected. The use of a water-soluble derivative of triptolide (Minnelide) in an animal model for over 300 days without any adverse effect on the normal physiology of the animals further indicates that this compound does not result in a global transcriptional shutdown and that an alternative mechanism of action exists for this compound at physiological doses (28). Triptolide is known to affect a number of prosurvival pathways in a cancer cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for most cancer cells, the LD 50 for triptolide has been found to be 100 nmol/liter (37), at which XPB remains unaffected. The use of a water-soluble derivative of triptolide (Minnelide) in an animal model for over 300 days without any adverse effect on the normal physiology of the animals further indicates that this compound does not result in a global transcriptional shutdown and that an alternative mechanism of action exists for this compound at physiological doses (28). Triptolide is known to affect a number of prosurvival pathways in a cancer cell.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has previously shown that triptolide induces tumor cell death by down-regulating HSPs (22,28,32). This down-regulation of HSP70 is mediated at the transcriptional level, and expression at both the mRNA and protein levels is reduced upon treatment with this compound.…”
Section: Triptolide Down-regulates Pro-proliferative Pathways Inmentioning
confidence: 98%
See 1 more Smart Citation
“…At present, ~40% of patients have metastatic disease, and these patients are primarily treated with palliative therapy (26). The current chemotherapeutic agent of choice for pancreatic cancer is gemcitabine, which was approved by the FDA in 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicated that TP can not only inhibit the proliferation of many different types of cancer cells in vitro, but also inhibit the growth and metastasis of solid tumors in vivo, including prostatic cancer, lung cancer, breast cancer, colon cancer and pancreatic cancer. Moreover, it can enhance the anti-tumor effects of cytotoxic agents and chemotherapeutic agents (Lee et al, 1999;Chang et al, 2000;Chan et al, 2001;Yang et al, 2003;Wang et al, 2009;Liu, 2011;Chugh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%